OVERGENERALIZATION IN SINGULAR/PLURAL NOUNS AND SUFFIXED NOUNS OF IELTS COURSE STUDENTS - Matiini, Gharizi (Jurnal Pendidikan Bahasa dan Sastra, 2016)
This study aims to investigate the morphological overgeneralization of IELTS students. It focuses on the singular/plural nouns and suffixed nouns that are overgeneralized by those students. Three students are chosen as the participants of the study by collecting their writing exercises. Three writing texts are gathered taken from several weeks and materials. The writings are analyzed by sorting the nouns they produced and categorizing them according to the singular/plural nouns and suffixed nouns. The results reveal that the students over extended the rules of singular/plural nouns and suffixed nouns. However, recovery occurs very varied in both singular/plural nouns and suffixed nouns. They tend to be better in mentioning singular/plural nouns, yet they are being selective and careful in writing suffixed nouns. In conclusion, even though the language learners can mark their overgeneralization, it is still difficult for them to recover their errors. It is recommended here that longitudinal study that has more time to examine students recovery from overgeneralization can be conducted for the further study to give more detail evidence in students’ overgeneralizations.Keywords: overgeneralization, singular/plural nouns, suffixed nouns